Targeted deletion of the epididymal receptor HE6 results in fluid dysregulation and male infertility. - Davies, B; Baumann, C; Kirchhoff, C; Ivell, R; Nubbemeyer, R; Habenicht, U; Theuring, F; Gottwald, U (2004)
Human epididymal protein 6 (HE6; also known as GPR64) is an orphan member of the LNB-7TM (B(2)) subfamily of G-protein-coupled receptors. Family members are characterized by the dual presence of a secretin-like (type II) seven-transmembrane (7TM) domain and a long cell adhesion-like extracellular domain. HE6 is specifically expressed within the efferent ductules and the initial segment of the epididymis, ductal systems involved in spermatozoon maturation. Here, we report that targeted deletion of the 7TM domain of the murine HE6 gene results in male infertility. Mutant mice reveal a dysregulation of fluid reabsorbtion within the efferent ductules, leading to a backup of fluid accumulation in the testis and a subsequent stasis of spermatozoa within the efferent ducts. The fertility phenotype of HE6 knockout mice identifies this receptor as a potential nonsteroidal, nontesticular target for future male contraceptives and identifies an in vivo function for a member of this unusual gene family.